2020
DOI: 10.1002/cam4.3466
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of tumor‐infiltrating immune cells of melanoma with overall survival by immunogenomic analysis

Abstract: AimsDifferent types of tumor‐infiltrating immune cells not only augment but also dampen antitumor immunity in the microenvironment of melanoma. Therefore, it is critical to provide an overview of tumor‐infiltrating immune cells in melanoma and explore a novel strategy for immunotherapies.MethodsWe analyzed the immune states of different stages in melanoma patients by the immune, stromal, and estimation of stromal and immune cells in malignant tumor tissues using expression data (ESTIMATE) scores. Immune cell t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 51 publications
2
18
0
Order By: Relevance
“…Different types of tumor-infiltrating immune cells can upregulate or downregulate melanoma immunity in the microenvironment. [ 54 ] By comparing the correlations of immune cells in the high- and low-risk groups, we found that immune cell infiltration was lower in the high-risk group than in the low-risk group. Immune cells are a major component of the tumor microenvironment and are closely related to tumor cell proliferation, treatment response, and prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Different types of tumor-infiltrating immune cells can upregulate or downregulate melanoma immunity in the microenvironment. [ 54 ] By comparing the correlations of immune cells in the high- and low-risk groups, we found that immune cell infiltration was lower in the high-risk group than in the low-risk group. Immune cells are a major component of the tumor microenvironment and are closely related to tumor cell proliferation, treatment response, and prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Luo et al displayed uveal melanoma patients' prognosis had close interactions with the immunodominant tumor environment [ 50 ]. Various immune cells contributes to the tumor progression of melanoma including adaptive immune CD8+ T-lymphocytes, macrophages, and so on [ 51 ]. Then we found that risk score was positively involved in the level of infiltration by various immune cells (CD4+ T cells, dendritic cells and so on).…”
Section: Discussionmentioning
confidence: 99%
“…Several computational methods, alternative ways to immunohistochemistry and flow cytometry [ 15 ], have been recently developed to derive tumor immune infiltrates using gene expression profiles of bulk tumors. In this study, we use the latest popular deconvolution method [ 16 20 ], CIBERSORTx [ 21 ], to investigate the immune patterns of tumors and analyze the relationship between immune composition and clinical features of osteosarcoma patients.…”
Section: Introductionmentioning
confidence: 99%